Depletion of Aneuploid Cells in Human Embryos and Gastruloids. Issue 8 (August 2021) - Yang, Min; Rito, Tiago; Metzger, Jakob; Naftaly, Jeffrey; Soman, Rohan; Hu, Jianjun; Albertini, David F.; Barad, David H.; Brivanlou, Ali H.; Gleicher, Norbert
Abstract : (Abstracted from Nat Cell Biol 2021;23:314–321) Despite it being current practice in vitro fertilization (IVF) protocols to exclude aneuploid embryos diagnosed through preimplantation genetic testing (PGT-A), it remains controversial whether or not this improves IVF outcomes. Both IVF pregnancies and spontaneous pregnancies demonstrate similar levels of mosaicism (12% vs 6.3%).